Lila Abu-Lughod, Veiled Sentiments. Honor and Poetry in a Bedouin Society, Berkeley, University of California Press, 1988, XIX + 317 pp., ilus., map., (Anthropology/Middle Eastern Studies/Women's Studies). - Castañeda Reyes, José Carlos (Estudios de Asia y África, 1989)
-